The Factors Related to Hypertension in Pregnancy - Shinta Novelia; Yenny Aulya; Wendy Nidsy Revita (KHD Production, 2023)
Background: Hypertension in pregnancy is a measurement of systolic blood pressure ≥ 140 mmHg and diastolic ≥ 90 mmHg during pregnancy. According to the Indonesian Health Profile (2015), the five biggest causes of maternal death are bleeding (28%), hypertension in pregnancy (25%), infections (11%), prolong labor (5%), and abortion (5%). Objective: This study aims to determine the factors associated with the incidence of hypertension in pregnancy in Harapan Jayakarta Hospital. Methodology: This research is an analytical method with a cross sectional study. The sample in this study was 190 pregnant women. The sampling technique is simple random sampling. The instrument is medical record data. Data were analyzed using chi square statistical test. Results: The results showed that there was a significant relationship between age (p = 0.001), employment status (p = 0.003), parity (p = 0.009), pregnancy interval (p = 0.003), history of diabetes mellitus (p = 0.038), obesity (p = 0.017), history of hormonal contraception (p = 0.044) with incidence hypertension in pregnancy. Conclusions and Recommendations: There was a significant relationship between age, occupational status, gravida status, pregnancy interval, history of diabetes mellitus, obesity and history of hormonal contraception with the incidence of hypertension in pregnancy. It is expected that health workers provide health education to anticipate complications in pregnancy and women are expected to carry out the health education provided. Keywords: hypertension in pregnancy; age; occupational status; gravida; pregnancy interval; history of diabetes mellitus; obesity; history of hormonal contraception.